Isolation of Leptospira licerasiae, Leptospira interrogans and Leptospira kmetyi From Apparently Healthy Companion Dogs Vaccinated for Leptospirosis - C. D. Gamage; J. E. Sykes; T. P. J. Athapattu; P. Senerathne; U. Karunadasa; M. Fuward; T. Herath; B. D. S. Muthusinghe; K. Yoshimatsu; N. Koizumi (Veterinary Medicine and Science)
ABSTRACT Animal reservoir hosts that shed pathogenic leptospires represent a considerable public health risk because they lack clinical signs of illness that might prompt handling precautions. In Sri Lanka, dog ownership is widespread. Dogs reside within homes and interact closely with humans, but they also roam freely in surrounding neighbourhoods. Dogs that carry pathogenic leptospires represent a source of environmental contamination and infection of domestic and livestock animals, posing a greater public health issue. The objectives of this study were to isolate and molecularly characterise leptospires from the blood and urine of 20 apparently healthy companion dogs vaccinated for leptospirosis using a 2‐serovar vaccine in Kandy, Sri Lanka. Urine and blood samples were subjected to culture for leptospires in an EMJH medium. Growth of pathogenic/intermediate‐pathogenic leptospires was confirmed using nested PCR assays targeting the flaB gene of P1 and P2 Leptospira subclades. Three (15%) of 20 urine specimens and one (5%) of 20 blood cultures yielded leptospires. Phylogenetic analysis revealed L. interrogans and L. kmetyi (P1 subclade) in urine specimens and L. licerasiae (P2 subclade) in the blood. Thus, despite vaccination, dogs in Sri Lanka can shed viable pathogenic/intermediate‐pathogenic leptospires, with associated public health implications.